Maximal functions: Poisson integrals on symmetric spaces - Stein, Elias M. (1976)
Let u be a harmonic function on a symmetric space which is the Poisson integral of a function f in L(p), 1 ≤ p ≤ ∞. Then u converges restrictedly and admissibly to f almost everywhere. This result is proved by obtaining an appropriate maximal theorem which takes into account the structure of the Poisson kernel.